Fiqh al-Akl and Islamic Religious Education: An Effort to Build Food Consumption Awareness Based on Islamic Values - Muhammad Sulaiman; Shubhi Mahmashony Harimurti; Farah Ayu Sholihah; Rosih Aprilyani (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
Fiqh al-Akl is not merely a branch of Islamic jurisprudence concerned with the legal rulings and etiquette of food consumption; rather, it represents a paradigm for viewing food within the broader Islamic worldview. Amid the modern consumption crisis—characterized by instant foods, chemical additives, and the ambiguity of product halal certification—Islamic Religious Education (PAI) plays a crucial role in shaping an Islamic awareness of consumption that goes beyond legal permissibility (halal) to encompass wholesomeness (thayyib) and ethical responsibility. This article aims to explore the contribution of Fiqh al-Akl to the development of the PAI curriculum and educational strategies for fostering responsible consumption behavior. Using a qualitative library-based approach, the article emphasizes the importance of integrating values of halal, barakah (blessing), and social accountability into the teaching of Islamic Religious Education.